PENGARUH PEMBELAJARAN AKTIVITAS BERMAIN ATLETIK TERHADAP KEMAMPUAN GERAK DASAR SISWA - Kharis Muhamad Taufik, - (2012)
This thesis istitledEffect ofLearningActivitiesAthleticto PlayStudentsBasicMovementOfabilities.Studiesin classV(five) first semester at Sirahcaielementary schoolin the Sumedang district. The problemin this studyare asfollows, "How does learningto playathleticsactivitiesonbasicmovement abilitiesof students?" The purposeof this studywas toobtain dataand informationon the effectof learningto playthe athleticactivitiesof thestudent's basicmovement abilitiesand to knowhow farand how big theimpact is. The research methodused experimental methodwithdesignthe pretestandpost test. Withthisexperimental method, the authors soughtto reviewsomethingby the incident(the effect oflearningto playathleticactivity) on the basis ofstudents'movement abilities. Furthermore,the samplein this study werefemale studentsclassV(five) first semester at Sirahcaielementaryschoolsin the Sumedang districtschool year2011/2012as many as20 students. The tests usedin this study isthe motorabilitytestsgeneral/basicmovement abilitiestestconsisting ofShuttleRun4 x10 meters, testthrowingcatch witha distance of1 meterwithwall, StorkBalanceStandPositionalandsprint30 meters.Once the research is tested, it can be concluded that learning to play athletic activities have a significant influence on the increase in the basic movement abilities of students semester 1 class V (five) Sirahcai elementary schools in the school year 2011/2012. This is evidentfrom the results ofthe calculationafterthe datawerenormally distributed, thentested byt-testimproved, it thitung =6.55and2.86on areal levelttabel=0.95 anddk= 19. Based on theresults of hypothesis testing, it can be assumed thatlearningto playathleticactivityclass V(five) SirahcaiElementary School in the SumedangDistrictinthe school year2011/2012itturned outthere was an increaseto thebasicmovement abilitiesof studentsat the school.